2001
DOI: 10.7175/fe.v2i1.717
|View full text |Cite
|
Sign up to set email alerts
|

I costi diretti dei servizi psichiatrici in un dipartimento di salute mentale

Abstract: The present study aimed to evaluate the mean unit cost of psychiatric services, broken down by type of output. The analysis concerned a psychiatric service (with a Psychiatric Ward in General Hospital (PWGH), a Day-Care Center, a Community Residential Facilitie (CRF) and a NHS Mental Center (NHSMC), located in the North of Italy, selected among the 14 participants of the SCORE (Schizophrenia COsts and REsources) project. The most important result of this study was to estimate a baseline unit cost which can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2004
2004
2007
2007

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
2
3
0
Order By: Relevance
“…The retrospective multicenter cost-of-illness study on 99 outpatients suffering from schizophrenia carried out by Tanicone et al (2000) demonstrated that more than half the total direct costs were attributable to community interventions. Similar findings were obtained in the retrospective phase of the Schizophrenia Consumption of Resources (SCORE) project (Garattini et al 2001).…”
supporting
confidence: 80%
See 2 more Smart Citations
“…The retrospective multicenter cost-of-illness study on 99 outpatients suffering from schizophrenia carried out by Tanicone et al (2000) demonstrated that more than half the total direct costs were attributable to community interventions. Similar findings were obtained in the retrospective phase of the Schizophrenia Consumption of Resources (SCORE) project (Garattini et al 2001).…”
supporting
confidence: 80%
“…Although differences in method must be considered, it should be easier to compare studies conducted in the same country. Our data can be compared with those of Tarricone et al (2000) and with the retrospective phase of the SCORE project (Garattini et al 2001). Although total costs per patient on a yearly basis are similar in all three analyses (*x7,500 in Tarricone et al 2000, andsc6,924 in Garattini et al 2001), there are differences in the contribution of some cost components to total costs.…”
Section: Lations Implemented During the Last 20 Years Than By Affluen...supporting
confidence: 52%
See 1 more Smart Citation
“…The full‐cost method was used for the analysis (8); this led to an estimated €272 for the average cost of a day‐hospital day, €204 a day in hospital, and €46 an outpatient consultation. The daily average costs of a day‐hospital day and a day in hospital do not include inpatient drug‐treatment expenditures and diagnostic and laboratory tests, because these were estimated separately (9).…”
Section: Methodsmentioning
confidence: 99%
“…There are many deficiencies of traditional cost methodologies utilized to date; some studies calculate the total expenditure of patient's care for a certain mental pathology, but they don't obtain unit costs per patient or per service; this fact doesn't allow using the results for cost-effectiveness analysis or in economic evaluations or in decision making about financing for example [12][13][14][15][16] . However, there are papers that calculate unit costs per patient or service but, most of them, are using tariffs or prices previously established; these figures are taken as valid but with their use, average costs are obtained that do not reveal the totality of emaciated resources by type of patient 12,[17][18][19][20][21][22][23] . In other cases, if unit costs are calculated, the budgetary expenditure has been taken as the total consumption of resources in each service, and unit costs are the result of dividing that amount between the number of patients who have used the service; this average cost is not correct since the consumption of resources will be different according to patient's pathology; let's think about one Mental Health Centre, a schizophrenic patient will receive treatment mainly with psychiatrist and nurse, but a depressive person will spend more time with psychologist, so the cost of both people will be completely different.…”
Section: Introductionmentioning
confidence: 99%